Report on the practice-in-industry training in fish preservation - Awatin, Felicidad (1953.)
Fish preservation pays an important role in the economic development of our country. It deals on the preservation of fish and other aquatic resources used for human consumption. The important purpose of this phase of food technology is to prevent waste of locally abundant food and improve the nutritional flavour of that food. Briefly speaking, preservation is any process that prevents food from spoilage. The principal methods of preserving fish are: application of heat, dehydration, smoking, canning, refrigeration, and application of chemicals or preservatives. The first month of apprenticeship dealt with the preservation of fish by means of canning in the home. Homecanning of fish may be defined as the process of preserving fishery products in hermetically sealed container done at home. Equipment for homecanning can be purchased by an average class family. The important equipment includes pressure cooker, can sealer, and tin cans. The first object of canning is the prevention of spoilage, through microbiological action; by placing the food in hermetically sealed and heat sterilize containers. All the utensils or equipment must be clean in order to avoid contamination.
Report (Undergraduate. Fish Preservation) University of the Philippines, College of Fisheries. 1953.
Keywords: Fish -- Preservation